Cytosolic Nipah Virus Inclusion Bodies Recruit Proteins Without Using Canonical Aggresome Pathways - Becker, Nico; Heiner, Anja; Maisner, Andrea (Frontiers in Virology, 2022)
Nipah virus (NiV) is a BSL-4 classified zoonotic paramyxovirus that causes respiratory or encephalitic diseases. A hallmark of NiV infections, as with all cell infections caused by non-segmented negative-strand RNA viruses, is the formation of cytoplasmic inclusion bodies (IBs). We previously showed that cytosolic NiV IBs, which are formed in infected cells or in cells minimally expressing the NiV nucleocapsid proteins, are associated with the microtubule-organizing center (MTOC) marker γ-tubulin. They also recruit overexpressed cytosolic proteins that are not functionally required for viral replication in IBs and that otherwise might form toxic protein aggregates. Therefore, NiV IBs are thought to share some functional properties with cellular aggresomes. The fact that aggresomes were not found in NiV-infected cells supports the idea that NiV IBs are successfully reducing the proteotoxic stress in infected cells. Only if the proteasome-ubiquitin system is artificially blocked by inhibitors, cellular aggresomes are formed in addition to IBs, but without colocalizing. Although both structures were positive for the classical aggresome markers histone deacetylase 6 (HDAC6) and Bcl-2-associated athanogene 3 (BAG3), they clearly differed in their cellular protein compositions and recruited overexpressed proteins to different extents. The further finding that inhibition of aggresome pathways by HDAC6 or microtubule (MT) inhibitors did neither interfere with IB formation nor with protein sequestration, strengthens the idea that cytosolic NiV IBs can assume some aggresome-like functions without involving active transport processes and canonical cellular aggresome pathways.